ENGLISH LANGUAGE LEARNING FROM STUDENTS' PERSPECTIVE: THE ABSENCE OF DIGITAL MEDIA AS A BARRIER TO TEACHING QUALITY - Nur Hanifa, Wanda; Rakhmawati, Rakhmawati; Widjajati, Budi; Muhtarom, Muhtarom (Universitas Putera Batam, 2025)
The integration of digital media in English language teaching (ELT) has been widely recognized for improving students’ motivation, engagement, and learning outcomes. However, few studies have examined how students perceive the absence of such media in their classrooms. This study investigated the perceptions of eighth-grade students at SMPN 13 Surabaya regarding the lack of digital media in English language learning. Guided by the Technological Pedagogical Content Knowledge (TPACK) framework, this quantitative study employed a structured 20-item questionnaire involving 48 participants. Data were analyzed using validity and reliability tests, descriptive statistics, and Pearson correlation in SPSS version 29. The results showed all items were valid and reliable (Cronbach’s Alpha: 0.824 for Media Use; 0.956 for Teaching Quality). Students generally viewed their teachers’ performance positively (M = 3.11) despite the infrequent use of digital media (M = 3.00). The correlation between media use and teaching quality was positive but very low and not statistically significant (r = 0.168, p > 0.05), possibly due to the small sample size and teachers’ adaptability to conventional methods. These findings highlight that while teacher competence remains central to teaching quality, integrating digital media can further enrich classroom engagement and learning effectiveness.